Crystal violet decolorization assay for rapid detection of multidrug-resistant Mycobacterium tuberculosis isolates: A multicenter study - Coban, Ahmet Yilmaz (2018)
Background: Effective control of tuberculosis is achieved by early diagnosis and drug susceptibility testing for initiation of appropriate treatment. The performance of crystal violet decolorization assay (CVDA) for susceptibility testing of Mycobacterium tuberculosis to isoniazid (INH) and rifampicin (RIF) was compared in a multicenter study. Methods: Seventy-two M. tuberculosis isolates were tested in two phases by CVDA. Results: In Phase I, the specificity, sensitivity, positive predictive value (PPV), negative predictive value (NPV), and agreement for INH were 100%, respectively. Specificity, sensitivity, PPV, NPV, and agreement for RIF were 98.2%, 100%, 94.1%, 100%, and 98.6%, respectively. In Phase II, specificity, sensitivity, PPV, NPV, and agreement were 98%, 100%, 95.4%, 100%, and 98.6% for INH, respectively. Specificity, sensitivity, PPV, NPV, and agreement for RIF were 96.3%, 88.2%, 88.2%, 96.3%, and 94.4%, respectively. Results in the study were obtained on average 10.9 ± 3.1 days in Phase I and 9.8 ± 2.2 days in Phase II. Conclusion: CVDA can be performed for drug susceptibility testing in developed and developing countries. In addition, further studies with larger sample size are needed for evaluation of this method.